A field guide for cancer diagnostics using cell‐free DNA: From principles to practice and clinical applications. Issue 3 (20th December 2017) - Volckmar, Anna‐Lena; Sültmann, Holger; Riediger, Anja; Fioretos, Thoas; Schirmacher, Peter; Endris, Volker; Stenzinger, Albrecht; Dietz, Steffen
Abstract: Recently, many genome‐wide profiling studies provided insights into the molecular make‐up of major cancer types. The deeper understanding of these genetic alterations and their functional consequences led to the discovery of novel therapeutic opportunities improving clinical management of cancer patients. While tissue‐based molecular patient stratification is the gold standard for precision medicine, it has certain limitations: Tissue biopsies are invasive sampling procedures carrying the risk of complications and may not represent the entire tumor due to underlying genetic heterogeneity. In this context, complementary characterization of genetic information in the blood of cancer patients can serve as minimal‐invasive 'liquid biopsy'. Fragments of circulating cell‐free DNA (cfDNA) are released from tissues of healthy individuals as well as cancer patients. The fraction of cfDNA that is released from primary tumors or metastases (i.e. circulating tumor DNA, ctDNA) represents genetic aberrations in cancer cells, which are a potential source for diagnostic, prognostic, and predictive biomarkers. Recent studies have demonstrated technical feasibility and clinical applications including detection of drug targets and resistance mutations as well as longitudinal monitoring of tumors under therapy. To this end, a variety of pre‐analytical procedures for blood processing, isolation and quantification of cfDNA are being employed and several analytical methods and technologies ranging from PCR‐based single locus assays to genome‐wide approaches are available, which considerably differ in sensitivity, specificity, and throughput. However, broad implementation of ctDNA analysis in daily clinical practice requires a thorough understanding of theoretical, technical, and biological concepts and necessitates standardization and validation of pre‐analytical and analytical procedures across different technologies. Here, we review the pertinent literature and discuss the advantages and limitations of available methodologies and their potential applications in molecular diagnostics.